18.2k views
3 votes
(05.02)

For the following system, if you isolated x in the first equation to use the Substitution Method, what expression would you substitute into the second equation? (5 points)

−x − 2y = −4
3x + y = 12

−2y − 4
2y − 4
2y + 4
−2y + 4

User Sceiler
by
6.1k points

1 Answer

7 votes

Answer:

4th option

Explanation:

From

- x - 2y = - 4 ( add x to both sides )

- 2y = x - 4 ( add 4 to both sides )

- 2y + 4 = x , so

Substitute x = - 2y + 4 into the second equation

User Adam Piotrowski
by
6.3k points